Prenatal echocardiographic diagnosis of double aortic arch. (9th March 2015) - Hunter, L.; Callaghan, N.; Patel, K.; Rinaldi, L.; Bellsham‐Revell, H.; Sharland, G.
ABSTRACT A double aortic arch is a congenital anomaly associated with the formation of a vascular ring, which can cause varying degrees of airway compression. This can be subclinical or clinical, manifesting as acute stridor, severe respiratory compromise or symptoms of chronic airway compression. An accurate diagnosis of double aortic arch can be made prenatally by fetal echocardiography. In this report, we describe two infants with normal karyotypes in whom a prenatal diagnosis of double aortic arch was made at our fetal cardiology center, between July 2012 and August 2013. The diagnosis was confirmed postnatally by two‐dimensional echocardiography and cardiac magnetic resonance imaging (MRI). The presence of a right aortic arch should prompt more careful evaluation to exclude a double aortic arch. Postnatal assessment should comprise echocardiography and cross‐sectional imaging in the form of cardiac MRI/computed tomography. Bronchoscopy may be considered to exclude subclinical airway compression and reduce potential long‐term respiratory sequelae. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.